Teen Titans go! Volume 3, Mumbo jumble - Fisch, Sholly; Hagan, Merrill; Cohen, Ivan; Nuhfer, Heather; Morrissey, Paul; Fridolfs, Derek (DC Comics, 2016)
The Titans face a pair of robotic teeth controlled by an alien virus and help cure Starfire's Tamaranean flu. Meanwhile, the team gets a chance at a Batmobile road trip and their own fairy godmother.